Rapid Assessment of Institutional Research Ethics Capacity: A Case Study from Zambia - Hyder, Adnan A.; Deutsch-Feldman, Molly; Ali, Joseph; Sikateyo, Bornwell; Kass, Nancy; Michelo, Charles (Acta Bioethica, 2017)
Recently, there has been a remarkable increase in biomedical research being conducted in low and middle-income countries. This increase has brought attention to the need for high quality research ethics systems within these countries and a greater focus on research ethics training. Though most programs tend to concentrate on training individuals, less attention has focused on institutions as the target of such training. In this paper we demonstrate a rapid approach to evaluating institutional research capacity. The method adapts the Octagon Model, which evaluates institutional research ethics using eight domains: basic values and identity, organization of activities, implementation, relevance, proper skills, financing and administration, target groups, and working environment. The framework was applied to the University of Zambia in order to conduct a baseline assessment of university research ethics capacity. Internal and external assessments were conducted. The domains of working environment and proper skills scored highest, while relevance, target groups and identity scored lower. Consistent with previous work, a systems approach to evaluating institutional research development capacity can provide a rapid assessment of an institutional bioethics program. This case study reveals the strengths and weaknesses of the university’s research ethics program and provides a framework for future capacity growth.